Supported ionic liquid and polymer inclusion membranes for metal separation. Issue 1 (2nd January 2022) - Zante, Guillaume; Boltoeva, Maria; Masmoudi, Abderrazak; Barillon, Rémi; Trébouet, Dominique
ABSTRACT: Background: Supported liquid membranes (SLMs) and polymer inclusion membranes (PIMs) are an interesting technology for the recovery and separation of metal ions. This kind of membranes could provide the advantages of hydrometallurgy ( i.e . high selectivity, possibility to treat low concentration of metals …) without needing a large organic solvent inventory. Problem: However, the large-scale application of SLMs is limited because of the short lifetime of the process. Several authors claimed a longer lifetime when molecular diluents were replaced by ionic liquids (ILs). Possible solutions: In this review, recent advances on the extraction of metals from aqueous solutions using SLMs and PIMs based on ILs are summarized and discussed. The mechanisms of degradation are reported and the improvements as well as limitations outlined. In SLMs, ILs were shown to improve membrane stability. However, stability is improved with viscous ILs having low solubility in water. ILs were used in PIMs as plasticizers and/or carriers and have shown their potential. However, the effect of ILs on PIM structure is not fully understood. To date, extraction of anionic metallic species is the most relevant field of study for SLMs and PIMs. A larger variety of ILs could be studied to apply this technique for a broader range of metals.